Changes in Archery Equipment in Eastern Europe of the IX-X Centuries According to Experimental Archaeology. Further Perspectives for Study through Archaeological Research and Observation - Türk Attila; Wilhelm Ákos S.; Paku Sándor (Поволжская археология, 2025)
Antler overlays-plates for strengthening bows, which appeared in the Hunnic period, underwent significant changes by the IX and X centuries and soon disappeared. There is an opinion that these ear and grip plates were used to strengthen the joints during bow making, and then with the development of new gluing methods the bows became much stronger and more durable making such overlays unnecessary. During the same period, the bowcase for carrying a strung bow appeared. Its use may have been made possible by changes in the design of bows that made them suitable to leave the bow strung for long periods of time. A bow that could be carried strung for long periods of time not only eliminated the need of stringing, but also gave the warrior a significant combat advantage.